BELIEFS AND DEPRESSIVE SYMPTOMS: PRELIMINARY RESULTS IN THE DEVELOPMENT OF A BRIEF IRRATIONAL BELIEFS SCALE - Calvete Zumalde, Esther; Cardeñoso Ramírez, Olga (Anales de Psicología / Annals of Psychology, 1999)
In this study we evaluated the measuring properties of a reduced version of the IBT (Irrational Beliefs Test, Jones, 1968) and of the CES-D (Center for Epidemiologic Studies Depression Scale, Radloff, 1977) as well as the association between both variables as derived from the Rational Emotional Therapy theory (Ellis, 1962). Thus 568 undergraduate students filled in the IBT and the CES-D. The factor analyses (LISREL8) confirmed an eight factor structure for the reduced version of the IBT (Need of Approval, High Self-expectations, Self-blame, Emotional Control, Problems Avoidance, Dependence on others, Helplessness about the change and Perfectionism). For the CES-D, it was confirmed a four factor structure of first order (Depressive Affect, Lack of positive Affection, Psychomotor decrease and Interpersonal difficulties) together with a factor of second order. The adaptation was good for the CES-D but only moderate for the IBT. Finally a model of structural equations was estimated between the irrational beliefs and depression. According to this model, the Need of Approval on the part of others, Perfectionism and Helplessness about the change appeared to be linked to the depressive symptoms.